Herd Behaviour and Capital market: a review of Literature - Sagar Varshney, Dr. T. Gurusant, Prof. Kanhaiya Singh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The herd behaviour in investment decisions is a process when large number of investors take a collective decision to invest their capital in the same stock at a time without using rational and differentiating between other investment options. Traditionally, this phenomenon was dominating on the higher side especially among the retail investors. But with an increased means of investors education and level of awareness, the extent of herd behaviour in investment decisions has been coming down. However, various studies undertaken in the past revealed mixed opinion where they find herd behaviour elements on the higher side in under developed markets as well among the lesser financially educated investors. The studies also evidenced that there are behavioural and psychological factors associated with the herd behaviour attitude and such factors are more dominant. This paper attempts to review the available literature on the subject to understand the trend of herd behaviour, factors influencing herd behaviour and attitude and approach of investors in investment decisions. The findings of various studies reveal the existence of herd behaviour to an extent among the retail investors and factors influencing include psychological and attitudinal